Analysis of heart rate and lactate concentrations during coordinative tasks: pilot study in karate kata world champions - Invernizzi, P. L.; Longo, S.; Scurati, R. (Sport Sciences for Health, 2008)
Kata, the artistic part of karate, requires motor control, rhythm and movement differentiation capacities. When performing in a synchronised manner, kata team members have to make temporal and spatial adaptations to satisfy the requested task. It is not clear whether these coordinative adaptations modify physical output such as heart rate (HR) and blood lactate ([La-]) nor is it known how rapidly top-level athletes adapt. This study examined HR and [La-] outputs in different coordinative tasks and how accurately these tasks were done, in three world champion kata team competitors. In session 1, athletes performed their individual best trial (IM) on Gankaku, the kata that is normally executed during final team events. In sessions 2 and 3, the athletes repeated the kata with temporal and spatial variations (TV10 and TV20, SV1 and SV2). In session 4, one maximal team trial (TM) was performed. There was a decreasing trend in both HR and [La-] across the trials (HR: -2% in TV10, -4.2% in TV20, -2.9% in SV1, -3.2% in SV2; [La-]: -23.6% in TV10, -32.6% in TV20, -18% in SV1, -15.9% in SV2), and between IM and TM (HR -9.9%; [La-] - 21.5%). The coordinative tasks were achieved with a small error (<3%) in all subjects. These results indicate that top-level kata athletes easily adapt to coordinative modifications, with a reduction in HR and [La-]. Although this decline does not compromise the competition results, it also occurs when the performance is executed synchronously in a team.